Structural rearrangements in contractile apparatus and resulting skeletal muscle remodelling: effect of exercise training - Seene, T.; Kaasik, P.; Umnova, M. (The Journal of Sports Medicine and Physical Fitness, 2009)
This review briefly summarizes studies that examine fast- and slow-twitch skeletal muscles and the ultra- and molecular structure of fibre types, including intrafusal fibres, during adaptation to exercise training. Adaptation capability of skeletal muscle to different types of exercise training depends on rearrangements in the contractile apparatus, mitochondria, other fibre organelles and neuromuscular junctions. Skeletal muscle functional capacity depends on structural changes in fibre organelles and is related to higher centres of motor control as the adaptation process needs information about muscle length and speed of contraction at any time during the training process. The renewal of the contractile apparatus in skeletal muscle during exercise training supports the qualitative remodelling of muscle so that the muscle contraction is better suited to the new conditions. The effectiveness of metabolic processes in new conditions depends on the structural-functional relationships between the energy system and contractile machinery in muscle fibres.